Economic Fallout of Covid-19: Evidence from South Africa - Ndzalama Mathebula; Baneng Naape (Profesional Muda Cendekia Publishing, 2023)
The covid 19 pandemic was quite challenging for policy makers in that it presented both an economic and health crisis. This meant that policy makers had to strike a balance between saving lives and protecting livelihoods. Against this backdrop, the primary goal of this study is to examine the economic fallout of covid 19 in South Africa. On the education front, the study finds that nearly 15% (2 million) of public-school pupils did not return to school post covid 19. Furthermore, the study finds that the covid 19 pandemic exacerbated the entrenched digital divide in the education system. As regards the economic implications of the covid 19 pandemic, the study found that business liquidations increased by as much as 48.9% following the outbreak of the covid 19 pandemic. Even worse, the total number of civil summonses issued for debt increased by 28.9% in the three months ending July 2021 compared to July 2020. Meanwhile, the value of civil judgements recorded for debt doubled from R483 million to R855 million during the same period. This indicates that following the outbreak of covid 19, a significant number of citizens were facing a litany of cash flow challenges amid reductions in salaries and forced retrenchments, hence the default in loan repayments. There remains a strong need for epidemic preparedness given that disease outbreaks are not likely to disappear in the near future. This can be achieved by harnessing lessons from previous pandemics and establishing effective surveillance and response systems.